Probiotic Gastrointestinal Transit and Colonization After Oral Administration: A Long Journey - Han, Shengyi; Lu, Yanmeng; Xie, Jiaojiao; Fei, Yiqiu; Zheng, Guiwen; Wang, Ziyuan; Liu, Jie; Lv, Longxian; Ling, Zongxin; Berglund, Björn; Yao, Mingfei; Li, Lanjuan (Frontiers in Cellular and Infection Microbiology, 2021)
Orally administered probiotics encounter various challenges on their journey through the mouth, stomach, intestine and colon. The health benefits of probiotics are diminished mainly due to the substantial reduction of viable probiotic bacteria under the harsh conditions in the gastrointestinal tract and the colonization resistance caused by commensal bacteria. In this review, we illustrate the factors affecting probiotic viability and their mucoadhesive properties through their journey in the gastrointestinal tract, including a discussion on various mucosadhesion-related proteins on the probiotic cell surface which facilitate colonization.